Dyadic relations of persons with disabilities: coping and psychological well-being - Shipova, Natalia; Sevastyanova, Ulyana (Social Welfare: Interdisciplinary Approach, 2019)
Studying the close relations of people with disabilities seems to us an important and socially acute problem with practical significance and meeting the social demand of the society. The study is devoted to the study of coping and psychological well-being of the dyad of persons with disabilities. Dyad groups of partners with normative and impaired development differ significantly in their main indicators (dyadic coping strategies, aspects of dyadic relations, level of well-being).